The genres of Late Antique Christian poetry: between modulations and transpositions - Hadjittofi, Fotini; Lefteratou, Anna (Trends in Classics - Supplementary Volumes, 2020)
Classicizing Christian poetry has largely been neglected by literary scholars, but has recently been receiving growing attention, especially the poetry written in Latin. One of the objectives of this volume is to redress the balance by allowing more space to discussions of Greek Christian poetry. The contributions collected here ask how Christian poets engage with (and are conscious of) the double reliance of their poetry on two separate systems: on the one hand, the classical poetic models and, on the other, the various genres and sub-genres of Christian prose. Keeping in mind the different settings of the Greek-speaking East and the Latin-speaking West, the contributions seek to understand the impact of historical setting on genre, the influence of the paideia shared by authors and audiences, and the continued relevance of traditional categories of literary genre. While our immediate focus is genre, most of the contributions also engage with the ideological ramifications of the transposition of Christian themes into classicizing literature. This volume offers important and original case studies on the reception and appropriation of the classical past and its literary forms by Christian poetry